Semiconductor surface spectroscopy using transverse acousto-electric effect: Role of surface charge in photo-processes at ZnS/Si interface - Tatyanenko, N.P.; Roshchina, N.N.; Gromashevskii, V.L.; Svechnikov, G.S.; Zavyalova, L.V.; Snopok, B.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The effect of illumination in the visible spectral range on the magnitude of transverse acoustoelectric effect (TAE) in ZnS/Si structures was studied using a noncontact surface acoustic wave device based on the acoustoelectronic structure with an air gap. ZnS films were obtained using pyrolysis of the chelate organometallic complex, zinc diethyldithiocarbamate, on Si substrates within the temperature range 220 to 260 °С. It has been established that the charge of the adsorption origin on the external surface of the ZnS film strongly influences the photo-processes in the structure under consideration. For samples with a small surface charge, the value of TAE decreases rapidly with increasing illumination power due to an increase in the concentration of non-equilibrium carriers. For the samples with a large surface charge, the barrier-trap mechanism of photogeneration is observed, in which the appearance of non-equilibrium carriers is accompanied by their capture and subsequent thermalization. This compensating mechanism explains well both stabilization of the magnitude of TAE by a distributed system of traps with rather large capacitance, and the specific shape of dependence of the TAE magnitude on illumination power. The technique developed by us on the basis of the transverse acoustoelectric effect in the layered piezodielectric / air-gap / semiconductor structure is a powerful tool for non-contact determination of the charge state of film structures, depending on their deposition parameters and various external conditions.